Adolescent development and sexual behavior: III. Sexual education in school - Di Pietro, Maria Luisa (Medicina e Morale, 1992)
The author analyses the Italian situation in relation to the insertion of sexual education in school. As far as Italy is concerned, after a brief evaluation of the adolescents' expectations about the intervention of the school in sexual education, the various interpretations of this subject that the DDL presented in Parliament are highlighted, but despite these differences a unified bill was drafted. At a European level the situation does not seem to be so clearly definied. In fact, in some countries there is no specific law on sexual education, while in the countries where sexual education is already compulsory in school, there is a wide margin for individual initiatives.